Song of St. Francis - Bulla, Clyde Robert; Angelo, Valenti 1897-. (New York Crowell, 1952)
A short biography of St. Francis telling how his father wanted him to become a rich prince but how Francis became a princely person who cared for the sick and needy and loved all animals.
Keywords: Francis, of Assisi, Saint -- 1182-1226.